Nimble adaptation: Tailoring monitoring, evaluation, and learning meth ods to provide actionable data in complex environments - Serpe, Lauren; Ingram, Mason; Byom, Kate (New Directions for Evaluation, 2022)
This chapter examines good practices in implementing effective Monitor ing, Evaluation, and Learning (MEL) systems within complex internation al development Democracy, Human Rights, and Governance (DRG) programs, which are characterized by challenges of non-linearity, limited evide nce of theories of change, and contextual and politically contingent n ature of outcomes. The chapter presents three cases of MEL systems in complex projects implemented by Pact across distinct and diverse opera ting contexts – Zimbabwe, Cambodia, and Somalia – to illustrate those projects’ MEL approaches that enabled continuous adaptation. The autho rs analyze the cases to respond to two questions: (1) What are the key elements of effective adaptive management-focused MEL systems in comp lex environments? (2) What is practical guidance for designing and ena bling complexity-responsive and effective adaptive management-focused MEL systems? The case studies illustrate three key elements: (1) Infor mation gathering that closely links context, research, and performance data; (2) Systems for reflection that offer scheduled learning moment s of varying frequency and intensity, as well as multiple feedback mec hanisms; and (3) Enabling structures that promote adaptive mindsets an d attitudes within project teams.